2006
DOI: 10.1289/ehp.8763
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Effects on Bone in a Population-Based Study of Women

Abstract: High cadmium exposure is known to cause bone damage, but the association between low-level cadmium exposure and osteoporosis remains to be clarified. Using a population-based women’s health survey in southern Sweden [Women’s Health in the Lund Area (WHILA)] with no known historical cadmium contamination, we investigated cadmium-related effects on bone in 820 women (53–64 years of age). We measured cadmium in blood and urine and lead in blood, an array of markers of bone metabolism, and forearm bone mineral den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
172
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(200 citation statements)
references
References 41 publications
13
172
3
4
Order By: Relevance
“…(3)(4)(5)(6) It should be noted, however, that our results indicate an increased risk of osteoporosis at considerably lower Cd exposures. In addition, the results for BMD at the lumbar spine may indicate a greater public health concern than recognized previously.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…(3)(4)(5)(6) It should be noted, however, that our results indicate an increased risk of osteoporosis at considerably lower Cd exposures. In addition, the results for BMD at the lumbar spine may indicate a greater public health concern than recognized previously.…”
Section: Discussioncontrasting
confidence: 65%
“…Human data support Cdinduced increased bone resorption rather than an effect on bone formation. (6,29,30) Our results on fracture risk suggest, however, that Cd's effect is only partly mediated via lowered BMD. It can be speculated that Cd exposure also results in specific effects on cortical and trabecular bone or in alterations of biomechanical properties that are not detected by DXA; this is also supported by experimental studies.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Clinical features associated with osteoporosis include increased morbidity (pain, physical impairment, decreased quality of life), increased risk of new fractures and increased mortality (Van der Klift et al 2002). Studies among populations from Belgium (Staessen et al 1999;Schutte et al 2008b), Sweden (Järup et al 1998a;Alfvén et al 2000;Å kesson et al 2006), Japan and China Jin et al 2004;Wang et al 2003) showed associations between osteoporosis and low-level environmental Cd exposure. The generally accepted interpretation has been that Cd-induced renal tubular damage (Staessen et al 1994) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria and decreased bone mineral density, and hence increased fracture risk (Järup et al 1998c;Staessen et al 1994) particularly in postmenopausal women (Schutte et al 2008b;Staessen et al 1999) or men in the older age group .…”
Section: Osteoporosismentioning
confidence: 99%